Impact of acute kidney injury and renal recovery status in deceased donor to kidney transplant outcome: results from the Thai national transplant registry - Nuttasith Larpparisuth; Supanit Nivatvongs; Kajohnsak Noppakun; Adisorn Lumpaopong; Cholatip Pongskul; Peenida Skulratanasak (Scientific Reports, 2023)
Abstract The influence of acute kidney injury (AKI) and renal recovery in deceased donor (DD) on long-term kidney transplant (KT) outcome has not previously been elucidated in large registry study. Our retrospective cohort study included all DDKT performed in Thailand between 2001 and 2018. Donor data was reviewed case by case. AKI was diagnosed according to the KDIGO criteria. Renal recovery was defined if DD had an improvement in AKI to the normal or lower stage. All outcomes were determined until the end of 2020. This study enrolled 4234 KT recipients from 2198 DD. The KDIGO staging of AKI was as follows: stage 1 for 710 donors (32.3%), stage 2 for 490 donors (22.3%) and stage 3 for 342 donors (15.6%). AKI was partial and complete recovery in 265 (17.2%) and 287 (18.6%) before procurement, respectively. Persistent AKI was revealed in 1906 KT of 990 (45%) DD. The ongoing AKI in DD significantly increases the risk of DGF development in the adjusted model (HR 1.69; 95% CI 1.44–1.99; p < 0.001). KT from DD with AKI and partial/complete recovery was associated with a lower risk of transplant loss (log-rank P = 0.04) and recipient mortality (log-rank P = 0.042) than ongoing AKI. KT from a donor with ongoing stage 3 AKI was associated with a higher risk of all-cause graft loss (HR 1.8; 95% CI 1.12–2.88; p = 0.02) and mortality (HR 2.19; 95% CI 1.09–4.41; p = 0.03) than stage 3 AKI with renal recovery. Persistent AKI, but not recovered AKI, significantly increases the risk of DGF. Utilizing kidneys from donors with improving AKI is generally safe. KT from donors with persistent AKI stage 3 results in a higher risk of transplant failure and recipient mortality. Therefore, meticulous pretransplant evaluation of such kidneys and intensive surveillance after KT is recommended.